A Randomised Controlled Trial Comparing Three Different Radiofrequency Technologies: Short-Term Results of the 3-RF Trial. (September 2019) - Nyamekye, Isaac K.; Dattani, Nikesh; Hayes, Wendy; Harding, Daniel; Holloway, Sarah; Newman, Jeremy
Abstract : Objective: To date there has been no comparison of outcomes of endovenous radiofrequency (RF) devices. The 3-RF trial is the first randomised controlled trial of three commercially available RF ablation technologies. Methods: Patients were recruited [182/302 patients with great saphenous vein (GSV) incompetence] into a prospective double blind randomised trial of Venefit, radiofrequency induced thermal therapy (RFITT), and endovenous radiofrequency (EVRF). The primary outcome measure was GSV closure (total/partial/failed) at six months. Secondary outcome measures included ablation times, complications, pain scores, analgesia requirements, and quality of life (QoL) scores to 12 months. Results: Patients treated [180: Venefit (57), RFITT (64), EVRF (59)] were matched for age, sex, and vein characteristics. At six months, complete GSV closure was significantly better after Venefit and RFITT treatment (100% and 98%, respectively) compared with EVRF treatment (79%, p < .001). Mean treatment time was significantly faster for RFITT than for Venefit and EVRF ( p < .0001). Euroqol 5D (EQ5D) visual analogue score (VAS) did not differ between groups at any time point. The only difference between groups in EQ5D domain scores was for the pain/discomfort domain at two weeks when significantly fewer EVRF patients reported no problems compared with Venefit and RFITT. This difference had disappeared at six and 12 months. The Aberdeen Varicose Vein Questionnaire (AVVQ) improved for all groups at six and 12 months compared with pre-treatment levels; however, there was no significant difference between groups. Conclusion: Compared with Venefit and RFITT, EVRF was associated with significant failure of truncal ablation at six months; however, clinical outcomes did not differ significantly at 12 months.clinicaltrials.gov identifier:NCT02441881, NHS Health Research Authority (Hampstead Research Ethics Committee) number: 14/LO/1232.